Effect of Metals on the Lytic Cycle of the Coccolithovirus, EhV86 - Gledhill, Martha; Devez, Aurelie; Highfield, Andrea; Singleton, Chloe; Achterberg, Eric P.; Schroeder, Declan (Frontiers in Microbiology, 2012)
In this study we show that metals, and in particular copper (Cu), can disrupt the lytic cycle in the Emiliania huxleyi - EhV86 host-virus system. Numbers of virus particles produced per E. huxleyi cell and E. huxleyi lysis rates were reduced by Cu at total metal concentrations over 500 nM in the presence of EDTA (ethylenediaminetetraacetic acid), and 250 nM in the absence of EDTA in acute short term exposure experiments. Zinc (Zn), cadmium (Cd) and cobalt (Co) were not observed to affect the lysis rate of EhV86 in these experiments. The cellular glutathione (GSH) content increased in virus infected cells, but not as a result of metal exposure. In contrast, the cellular content of phytochelatins (PCs) increased only in response to metal exposure. The increase in gluthatione content is consistent with increases in the production of reactive oxygen species (ROS) on viral infection, while increases in PC content are likely linked to metal homeostasis and indicate that metal toxicity to the host was not affected by viral infection. We propose that Cu prevents lytic production of EhV86 by interfering with virus DNA (deoxyribonucleic acid) synthesis through a transcriptional block, which ultimately suppresses the formation of ROS, a biochemical response required for successful virus infection.